The influence of aging on the number of neurons and levels of non-phosporylated neurofilament proteins in the central auditory system of rats - Burianová, Jana; Ouda, Ladislav; Syka, Josef (Frontiers in Aging Neuroscience, 2015)
In the present study, an unbiased stereological method was used to determine the number of all neurons in Nissl stained sections of the inferior colliculus (IC), medial geniculate body (MGB), and auditory cortex (AC) in rats (strains Long Evans and Fischer 344) and their changes with aging. In addition, using the optical fractionator and western blot technique, we also evaluated the number of SMI-32-immunoreactive (-ir) neurons and levels of non-phosphorylated neurofilament proteins in the IC, MGB, AC, and visual cortex of young and old rats of the two strains. The SMI-32 positive neuronal population comprises about 10% of all neurons in the rat IC, MGB, and AC and represents a prevalent population of large neurons with highly myelinated and projecting processes. In both Long Evans and Fischer 344 rats, the total number of neurons in the IC was roughly similar to that in the AC. With aging, we found a rather mild and statistically non-significant decline in the total number of neurons in all three analyzed auditory regions in both rat strains. In contrast to this, the absolute number of SMI-32-ir neurons in both Long Evans and Fischer 344 rats significantly decreased with aging in all the examined structures. The western blot technique also revealed a significant age-related decline in the levels of non-phosphorylated neurofilaments in the auditory brain structures, 30–35%. Our results demonstrate that presbycusis in rats is not likely to be primarily associated with changes in the total number of neurons. On the other hand, the pronounced age-related decline in the number of neurons containing non-phosphorylated neurofilaments as well as their protein levels in the central auditory system may contribute to age-related deterioration of hearing function.